The Effectiveness of Problem Based Learning Method on Students’ Achievement in An Analog Electronics Course at Palestine Polytechnic University - Arman, Abdallah Moh’d (Discoveries in Agriculture and Food Sciences, 2019)
This study, undertaken at the Palestine Polytechnic University in Palestine, describes how problem-based learning (PBL) affects the Students’ Achievement in ‘analog electronics course’. Problems were designed to match real-life situations. Data of the experimental group learning outcome effects, were compared.. It was found that students who followed the PBL method learned to do research, learned better how to work in groups and developed greater confidence. Also what they learned was more of a practical value and they had more positive attitudes and reflected more. This research is in response to the real need to address gaps between employer expectations and higher education outcomes in Palestine. In this study, an experimental group of (16) students was examined after studying a course using PBL approach. The students’ achievement was examined before and after the experiment. The research results proved that there is a significant increase in gain in achievement. The PBL has achieved efficiency greater than (80%) in achievement. Also, the PBL has achieved efficiency greater than (1.2) measured with respect to Black’s Gain Ratio in achievement. Also, PBL has achieved efficiency greater than (0.6) measured with respect to McGugian’s Gain Ratio in achievement. The PBL has achieved larger effect size (more than 0.14) on achievement.